2015
DOI: 10.1097/ccm.0000000000000947
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia for Traumatic Brain Injury in Children—A Phase II Randomized Controlled Trial*

Abstract: Early therapeutic hypothermia in children with severe traumatic brain injury does not improve outcome and should not be used outside a clinical trial. Recruitment rates were lower and outcomes were better than expected. Conventional randomized controlled trials in children with severe traumatic brain injury are unlikely to be feasible. A large international trials group and alternative approaches to trial design will be required to further inform practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Limitations to our study not mentioned previously include those inherent to the retrospective observational design. The population in this study was more heterogeneous than other published studies of children with severe TBI, as we did not exclude young infants(39, 40), patients with known or suspected child abuse(3942), patients with isolated acute epidural hematoma(39, 40), or patients without abnormalities on the first CT scan(39, 40, 42). The median ICU length of stay that we found, 4 days, was longer than that reported in a single-center retrospective cohort study (2 days)(41) but shorter than investigators observed in a multi-center efficacy trial (11 days) with a more homogeneous study population and a temperature-control protocol that could lengthen the ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations to our study not mentioned previously include those inherent to the retrospective observational design. The population in this study was more heterogeneous than other published studies of children with severe TBI, as we did not exclude young infants(39, 40), patients with known or suspected child abuse(3942), patients with isolated acute epidural hematoma(39, 40), or patients without abnormalities on the first CT scan(39, 40, 42). The median ICU length of stay that we found, 4 days, was longer than that reported in a single-center retrospective cohort study (2 days)(41) but shorter than investigators observed in a multi-center efficacy trial (11 days) with a more homogeneous study population and a temperature-control protocol that could lengthen the ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TBI represents a significant cause of morbidity and mortality in children admitted to the PICU (31,36,42,100). As shown in other fields, protocolized care and adherence to guidelines, even if of low evidence level, can be associated with improved outcomes.…”
Section: Neurologic Outcomes Following Picu Carementioning
confidence: 99%
“…Unfortunately, although these studies provided encouraging support for a role of hypothermia in the clinic, when this experimental therapy was tested in several multicenter trials, no benefits on neurological outcome were seen in severe TBI patients (Adelson et al, 2013; Beca et al, 2015). Three multicenter studies found either no difference or worse mortality rates in the hypothermia group compared to normothermia (Clifton et al, 2001b; Clifton et al, 2011; Maekawa, 2015; Maekawa et al, 2015).…”
Section: Clinical Tbi Studies With Hypothermiamentioning
confidence: 99%